Memaksimalkan Kemampuan Guru dalam Menganalisis SK-KD melalui Diskusi - suhaimi, suhaimi (Jurnal Daya Saing, 2016)
Abstract: The ability of teachers in analyzing SK-SD a separate issue in school, the study was conducted in SMP N 2 Mount Sahilan, based on the phenomenon of still optimal capability of teachers in preparing SK-SD. This study uses the discussion in order to improve the ability of teachers to analyze SK-SD. This type of research is action research school with the results showed that the teacher gives a positive response to the draft action research compiled by the supervisor to improve the ability of teachers to prepare lesson plans, especially in the analysis / assessment tehadap Competency Standards and Basic Competence in order to develop the syllabus. The guidance that supervisors as research followed by teachers in earnest. Keywords: Capability Teachers, Discussions